The distance between points A(x1, y1) and B(x2, y2) is given by sqrt[(x1 - x2)^2 + (y1 - y2)^2]

Here the points we have to the distance between are (1, 2) and (-2, 2).

The required distance between them is sqrt[(1 - (-2))^2 + (2 - 2)^2]

=> sqrt[(1 + 2)^2 + (2 - 2)^2]

=> sqrt[3^2 + 0^2]

=> sqrt[9 + 0]

=> sqrt 9

=> 3

**The distance between the points (1, 2) and (-2, 2) is equal to 3.**

if (x1,y1)=(1,2) and (x2,y2)=(-2,2)

distance=sqr root ((x2-x1)^2+(y2-y1)^2)

distance=sqr root((-2-1)^2+(2-2)^2)

distance=sqr root((-3)^2)

distance=3

To determine the distance between the given points, we'll recall the formula of the distance:

d = sqrt[(xB - xA)^2 + (yB - yA)^2]

Let A(1,2) => xA = 1 and yA = 2

Let B(-2,2) => xB = -2 and yB = 2

d = sqrt[(-2 - 1)^2 + (2 - 2)^2]

d = sqrt[(-3)^2]

d = sqrt9

**The length of the segment that represents the distance between the given points is d = sqrt9 units.**